E2/E3‐independent ubiquitin‐like protein conjugation by Urm1 is directly coupled to cysteine persulfidation. (14th September 2022) - Ravichandran, Keerthiraju E; Kaduhr, Lars; Skupien‐Rabian, Bozena; Shvetsova, Ekaterina; Sokołowski, Mikołaj; Krutyhołowa, Ros´cisław; Kwasna, Dominika; Brachmann, Cindy; Lin, Sean; Guzman Perez, Sebastian; Wilk, Piotr; Kösters, Manuel; et al.
Abstract: Post‐translational modifications by ubiquitin‐like proteins (UBLs) are essential for nearly all cellular processes. Ubiquitin‐related modifier 1 (Urm1) is a unique UBL, which plays a key role in tRNA anticodon thiolation as a sulfur carrier protein (SCP) and is linked to the noncanonical E1 enzyme Uba4 (ubiquitin‐like protein activator 4). While Urm1 has also been observed to conjugate to target proteins like other UBLs, the molecular mechanism of its attachment remains unknown. Here, we reconstitute the covalent attachment of thiocarboxylated Urm1 to various cellular target proteins in vitro, revealing that, unlike other known UBLs, this process is E2/E3‐independent and requires oxidative stress. Furthermore, we present the crystal structures of the peroxiredoxin Ahp1 before and after the covalent attachment of Urm1. Surprisingly, we show that urmylation is accompanied by the transfer of sulfur to cysteine residues in the target proteins, also known as cysteine persulfidation. Our results illustrate the role of the Uba4‐Urm1 system as a key evolutionary link between prokaryotic SCPs and the UBL modifications observed in modern eukaryotes. Synopsis: The ancient ubiquitin‐like protein Urm1 is a sulfur carrier protein for tRNA thiolation, but can also conjugate to target proteins. Here, analysis of the underlying molecular mechanisms reveals that Urm1 attachment simultaneously leads to the persulfidation of cysteines in target proteins, which may protect them from oxidative damage. In vitro ubiquitin‐like conjugation by Urm1 does not require E2 conjugation enzymes or E3 ligases. Urm1 conjugation depends on a peroxidatic cysteine in the target protein and the proximity of lysine, serine or threonine residues. Sulfur transfer from the thiocarboxylated C‐terminus of Urm1 onto cysteines in the target proteins is a mechanistic consequence of the urmylation reaction. High‐resolution crystal structure of an urmylated target protein directly shows formation of an iso‐peptide bond as well as cysteine persulfidation. The Urm1 pathway represents a distinct cysteine persulfidation pathway upon oxidative stress. Abstract : Mechanistic analysis of conjugation of the ancient ubiquitin‐like protein Urm1 reveals that its attachment simultaneously leads to the persulfidation of cysteines in the target proteins.